2024
DOI: 10.1209/0295-5075/ad1dea
|View full text |Cite
|
Sign up to set email alerts
|

Note on an extended chiral bosons system contextualized in a modified gauge-unfixing formalism

Gabriella V. Ambrósio,
Cleber N. Costa,
Paulo R. F. Alves
et al.

Abstract: We analyze the Hamiltonian structure of an extended chiral bosons theory in which the self-dual constraint is introduced via a control α-parameter. The system has two second-class constraints in the non-critical regime and an additional one in the critical regime. We use a modified gauge-unfixing (GU) formalism to derive a first-class system, disclosing hidden symmetries. To this end, we choose one of the second-class constraints to build a corresponding gauge symmetry generator. The worked out procedure conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…However kinetic energy-like terms [29], and even the combination of mass-like and kinetic energy-like terms [33] are found to materialize as a counter term. A very recent study related to gauge symmetry (gauge unfixing) of chiral bosons is found in [34] and similar types of studies on non-commutative chiral boson is considered in [35]. Application of the gauge unfixing in the chiral Schwinger model is reported in [36].…”
Section: Introductionmentioning
confidence: 89%
“…However kinetic energy-like terms [29], and even the combination of mass-like and kinetic energy-like terms [33] are found to materialize as a counter term. A very recent study related to gauge symmetry (gauge unfixing) of chiral bosons is found in [34] and similar types of studies on non-commutative chiral boson is considered in [35]. Application of the gauge unfixing in the chiral Schwinger model is reported in [36].…”
Section: Introductionmentioning
confidence: 89%